Nosotras cosechamos lo que otros botan”: la recuperación de alimentos que impulsan las ollas comunes desde el campo - International Potato Center (2025)
The article reports on the Red de Ollas de Pachacámac (Redopa), where women brigades recover surplus food from farms and markets to supply community kitchens in Lima, Peru. Despite a 2022 food rescue law, state agencies have not implemented it, so grassroots groups continue organizing. The initiative reduces waste, provides food security, and benefits farmers by saving costs on field clean-up. Supported by Fundación Avina, OIT, Fondo Canadá, and CIP, the model strengthens resilience, nutrition, and community solidarity.